Architectural Features and Resistance to Food-Grade Disinfectants in Listeria monocytogenes-Pseudomonas spp. Dual-Species Biofilms - Rodríguez-López, Pedro; Rodríguez-Herrera, Juan José; López Cabo, Marta (Frontiers in Microbiology, 2022)
Listeria monocytogenes is considered a foodborne pathogen of serious concern capable of forming multispecies biofilms with other bacterial species, such as Pseudomonas spp., adhered onto stainless steel (SS) surfaces. In an attempt to link the biofilms’ morphology and resistance to biocides, dual-species biofilms of L. monocytogenes, in co-culture with either Pseudomonas aeruginosa, Pseudomonas fluorescens, or Pseudomonas putida, were assayed to ascertain their morphological characteristics and resistance toward benzalkonium chloride (BAC) and neutral electrolyzed water (NEW). Epifluorescence microscopy analysis revealed that each dual-species biofilm was distributed differently over the SS surface and that these differences were attributable to the presence of Pseudomonas spp. Confocal laser scanning microscopy (CLSM) assays demonstrated that despite these differences in distribution, all biofilms had similar maximum thicknesses. Along with this, colocalization analyses showed a strong trend of L. monocytogenes to share location within the biofilm with all Pseudomonas assayed whilst the latter distributed throughout the surface independently of the presence of L. monocytogenes, a fact that was especially evident in those biofilms in which cell clusters were present. Finally, a modified Gompertz equation was used to fit biofilms’ BAC and NEW dose-response data. Outcomes demonstrated that L. monocytogenes was less susceptible to BAC when co-cultured with P. aeruginosa or P. fluorescens, whereas susceptibility to NEW was reduced in all three dual-species biofilms, which can be attributable to both the mechanism of action of the biocide and the architectural features of each biofilm. Therefore, the results herein provided can be used to optimize already existing and develop novel target-specific sanitation treatments based on the mechanism of action of the biocide and the biofilms’ species composition and structure.